Passive SOBP generation from a static proton pencil beam using 3D-printed range modulators for FLASH experiments - Horst, Felix; Beyreuther, Elke; Bodenstein, Elisabeth; Gantz, Sebastian; Misseroni, Diego; Pugno, Nicola M.; Schuy, Christoph; Tommasino, Francesco; Weber, Uli; Pawelke, Jörg (Frontiers in Physics, 2023)
The University Proton Therapy facility in Dresden (UPTD), Germany, is equipped with an experimental room with a beamline providing a static pencil beam. High proton beam currents can be achieved at this beamline which makes it suitable for FLASH experiments. However, the established experimental setup uses only the entrance channel of the proton Bragg curve. In this work, a set of 3D-printed range modulators designed to generate spread out Bragg peaks (SOBPs) for radiobiological experiments at ultra-high dose rate at this beamline is described. A new method to optimize range modulators specifically for the case of a static pencil beam based on the central depth dose profile is introduced. Modulators for two different irradiation setups were produced and characterized experimentally by measurements of lateral and depth dose distributions using different detectors. In addition, Monte Carlo simulations were performed to assess profiles of the dose averaged linear energy transfer (LETD) in water. These newly produced range modulators will allow future proton FLASH experiments in the SOBP at UPTD with two different experimental setups.